Commodity futures and momentum trading: implications for behavioural finance - Calder, Dan; O'Grady, Thomas (Barry) (School of Economics and Finance, Curtin Business School, 2009)
The purpose of this paper is to expand the research on momentum strategies in the securities market. Specifically, it examines the momentum anomaly in respect to the commodity futures market, and closely follows recent work as studied by Miffre and Rallis (2007). This study identifies one statistically significant short term (1 to 12 months) momentum strategy yielding a return of 7.7% a year. This return is found to be substantially higher during specific periods of the sample. The strategy?s average abnormal gain caused by the continuation of returns is shown to be robust to the risk based explanations posited by many authors of the topic. Since the risk explanations do not hold for the momentum anomaly, the alternative explanation indicates towards market inefficiency. The results from this study indicate that market inefficiency is a plausible explanation for momentum profits as realised. Specifically, the abnormal profits seem to be a consequence of irrational investor behaviour, which tends to lead to an under-reaction to new market information.